UPAYA PEMERINTAH DAERAH DALAM MENGEMBANGKAN PARIWISATA DI KABUPATEN BUTON TENGAH - Suriyani BB; La Manguntara; Hainun; Muhammad Zein Abdullah (Halu Oleo University, 2022)
The purpose of this research is to find out the efforts of the local government in developing tourism in Central Buton Regency and to find out the factors that hinder the local government in developing tourism in Central Buton Regency. The technique used in this research is qualitative research. Data collection techniques are carried out by means of library research and field research using interview, observation and documentation methods. The results of this study indicate that the Tourism Development Efforts in Central Buton Regency are divided into three namely a) making regulations, b) providing facilities and infrastructure and c). making plans while the Obstacles to Tourism Development Efforts in Central Buton Regency are divided into five namely a). Lack of Community Participation in the Tourism Sector b). There is no Attractive Promotion System yet, c) Limited work facilities and infrastructure at related agencies and tourist attractions, d) Lack of cooperation with investors, and e). Limitations and lack of maintenance of tourist attraction supporting facilities.